Identification of Submergence-Responsive MicroRNAs and Their Targets Reveals Complex MiRNA-Mediated Regulatory Networks in Lotus (Nelumbo nucifera Gaertn) - Jin, Qijiang; Xu, Yingchun; Mattson, Neil; Li, Xin; Wang, Bei; Zhang, Xiao; Jiang, Hongwei; Liu, Xiaojing; Wang, Yanjie; Yao, Dongrui (Frontiers in Plant Science, 2017)
MicroRNAs (miRNAs) are endogenous noncoding RNAs with important regulatory functions in plant development and stress responses. However, their population abundance in lotus (Nelumbo nucifera Gaertn) has so far been poorly described, particularly in response to stresses. In this work, submergence-related miRNAs and their target genes were systematically identified, compared and validated at the transcriptome-wide level using high-throughput sequencing data of small RNA, mRNA and the degradome. A total of 128 known and 20 novel miRNAs were differentially expressed upon submergence. We identified 629 target transcripts for these submergence-responsive miRNAs. Based on the miRNA expression profiles and GO and KEGG annotation of miRNA target genes, we suggest possible molecular responses and physiological changes of lotus in response to submergence. Several metabolic, physiological and morphological adaptations-related miRNAs, i.e. NNU_far-miR159, NNU_gma-miR393h, and NNU_aly-miR319c-3p, were found to play important regulatory roles in lotus response to submergence. This work will contribute to a better understanding of miRNA-regulated adaption responses of lotus to submergence stress.